COLOMBIANS’ SITUATION REGARDING PALLIATIVE CARE: PERSPECTIVE OF A NURSING PROFESSIONAL (Revista Universidad Católica de Oriente, 2020)
Despite the existence of specific legislation in Colombia regarding palliative care of patients with chronic and/or terminal diseases, the majority of Colombians do not have access to these services and both patients and their families lack this important support in this life process.